(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
As products of the waves of deregulation and liberalization of trade and investments in the region in the 1980s and mid-1990s, special economic zones (SEZs) have emerged as an important tool of economic governance in East and Southeast Asia. Recently, governments and investors around the region, have favored multi-purpose SEZs conceived for land and real estate development which exhibit several similarities such as eliciting tourism as the main driver of local development and a declared “eco” and “green” configuration. The Incheon Free Economic Zone (IFEZ) in the Republic of Korea (ROK) and the Van Don SEZ in the Socialist Republic of Vietnam (SRV) are two illustrative cases of urban policy diffusion as a complex phenomenon combining the ROK’s increased international activism and SRV’s own institutional structure and preferences in terms of development goals. Based on a close reading of reports, official documents, qualitative interviews and site visits, this article will further contribute to the debate on the complexity of urban policy diffusion in contemporary East and Southeast Asia.